AN ANALYSIS OF STANDARD ENGLISH AND GENERAL AMERICAN VARIETIES IN TEACHING SPEAKING OF FKIP UIR-PEKANBARU - Estika Satriani; Afrizal Afrizal; Arimuliani Ahmad (Universitas Negeri Padang, 2015)
Standard English and General American are part of varieties of English that are used and learned in education world. Formerly only Standard English had been taught, but lcently General American has been taWht as well. Nowadays, both varieties of General American and Standard English are found in university